Falling radionuclides activity calculation in circumstances of wreck on atomic reactor - Канунніков, Б. Т.; Жижченко, О. П.; Лук’янчиков, В. А.; Применко, В. І. (Proceedings of National Aviation University, 2021)
The methodics of falling radionuclides activity calculation and equal radiation dose in the rad aactive contamination zone is represented asa a function of total and individual radionuclides impact. The equation for analising the speed of falling of radionuclides activity in time is derived.